Highly flexible phosphabenzenes: a missing coordination mode of 2, 4, 6-triaryl-λ3-phosphinines. Issue 42 (27th April 2022) - Yue, Erlin; Petrov, Andrey; Frost, Daniel S.; Dettling, Lea; Conrad, Lawrence; Wossidlo, Friedrich; Coles, Nathan T.; Weber, Manuela; Müller, Christian
Abstract : The reaction of a phosphinine-Cr(CO)3 -π-complex with [Rh(COD)2 ]BF4 leads to an unusual Rh 0 -dimer, that contains two phosphinine-π-complexes acting each as a bridging 2e − ligand towards the Rh2 (CO)2 core. This compound represents a missing coordination mode of the aromatic phosphorus heterocycle. Abstract : The reaction of 2, 4, 6-triaryl-λ 3 -phosphinine-Cr(CO)3 -π-complexes with [Rh(COD)2 ]BF4 leads to unusual diamagnetic Rh 0 -dimers, which contain two phosphinine-π-complexes acting as a bridging 2e − -ligand towards the Rh2 (CO)2 core. These compounds represent a missing coordination mode for the aromatic 6-membered phosphorus heterocycle.